Strengthening One Health through rangelands stewardship - Ebro, Abule (CGIAR System Organization, 2025)
The HEAL (One Health for Human, Environment, Animal, and Livelihoods) project has established community rangeland health workers to provide rangeland health services. The initiative and progress made were presented at the Ethiopian Society for Animal Production, Ethiopia, 2025.